Relationship of Various Prognostic Factors with Outcome of Treatment of Chronic Duodenal Ulcer Perforation Patients (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Background: In acute abdominal conditions, chronic duodenal ulcer  perforation is a very common surgical emergency that overwhelm the surgical ward throughout the year. Especially in the tropics and more in our country, peptic ulcer disease causes a major health problem. Objectives: To assess the usefulness of the prognostic factors in terms of morbidity and mortality in the treatment of perforated duodenal ulcer patient. Methods: This was a prospective study during the period from January 2003 to December 2003 in M.A.G. Osmani Medical College Hospital, Sylhet. The study included 100 cases of perforated chronic duodenal ulcer. Patients were randomly collected from all surgical units of SOMCH, Sylhet. Operation was done by simple closure with omental graft in all cases. Data analyzed by appropriate statistical method (Mean, SD & l2 test). Results: Highly significant relationship was found between increased age (>50 years) of patients with perforated duodenal ulcer and mortality (p